This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ( t ). Similarly, let b k denote the Fourier series coecients of y ( t ). 1. Suppose x ( t ) = y ( t ). Is a k = b k for all k ? Is T x = T y ? 2. Suppose a k = b k for all k . Is x ( t ) = y ( t )? (Hint: Consider two cases, T x = T y and T x 6 = T y .) Question 3: p. 255, Problem 3.22(c). Question 4: p. 256, Problem 3.23(a). (Hint: Use techniques similar to Example 3.6.) Question 5: p. 256, Problem 3.28(a) with Fig. P3.28(b). Problem 3.28(d). Question 6: p. 256, Problem 3.29(b,c)....
View Full Document
This note was uploaded on 05/02/2009 for the course ECE 301 taught by Professor V."ragu"balakrishnan during the Spring '06 term at Purdue University-West Lafayette.
- Spring '06